Octreotide Does Not Inhibit Proliferation in Five Neuroendocrine Tumor Cell Lines - Exner, Samantha; Prasad, Vikas; Wiedenmann, Bertram; Grötzinger, Carsten (Frontiers in Endocrinology, 2018)
Somatostatin analogs (SSA) are well-established antisecretory drugs in functionally active neuroendocrine tumors (NET). Two placebo-controlled trials have recently demonstrated significant improvement of progression-free survival under SSA treatment. Furthermore, somatostatin receptor (SSTR) overexpression in NET has also been utilized for diagnostic imaging and peptide receptor radionuclide therapy (PRRT). However, PRRT in NET is associated mostly with partial and minor remission, while other radionuclide therapies reach complete remissions in up to 75 % of cases. This study assessed a potential radiosensitizing effect of SSA treatment in five established NET cell line models: BON, QGP-1, LCC-18, H727 and UMC-11. Irradiation was found to significantly inhibit proliferation, while no additional effect by octreotide treatment was observed. Intriguingly, no impact of SSA treatment alone was found in any of these NET cell lines when systematically analyzing cell viability, proliferation and cell cycle distribution. Investigation of the causes for this octreotide resistance led to demonstration of low octreotide binding and scarce SSTR, specifically SSTR2 expression as compared to levels found in human NETs. The resistance towards SSA treatment in viability and proliferation assays could not be overcome by re-expression of SSTR2 in two of the cell lines. These results provide systematic evidence for a lack of authentic, tumor-like SSTR expression and function in five frequently used NET cell line models and point to the need for more physiologic tumor model systems.